High-cycle fatigue strength of a pultruded composite material - L. Vergani; M.Guagliano; C. Colombo (Fracture and Structural Integrity)
Dealing with composites in polymeric matrix, the pultruded ones are among the more suitable for large production rates and volumes. For this reason, their use is increasing also in structural applications in civil and mechanical engineering. However, their use is still limited by the partial knowledge of their fatigue behaviour; in many applications it is, indeed, required a duration of many millions of cycles, while most of the data that can be found in literature refer to a maximum number of cycles equal to 3 millions. In this paper a pultruded composite used for manufacturing structural beams is considered and its mechanical behaviour characterized by means of static and high-cycle fatigue tests. The results allowed to determine the S-N curve of the material and to assess the existence of a fatigue limit. Observations at the scanning electronic microscope (SEM) allowed to evaluate the damage mechanisms involved in the static and fatigue failure of the material.